AB0712 Long-term safety and immunogenicity of the pandemic unadjuvanted influenza A/H1N1 vaccine in primary sjÖgren's syndrome. (23rd January 2014) - Pasoto, S.G.; Ribeiro, A.C.; Viana, V.S.; Barbosa, J.A.; Bueno, C.; Levy Neto, M.; Bonfa, E.
Abstract : Background: Despite WHO recommendations about the A/California/7/2009/H1N1-like virus vaccination, there are no studies evaluating its possible influence on clinical manifestations and autoantibody profile in primary Sjögren's syndrome (pSS). Objectives: To evaluate short/long-term safety and influence of influenza A/California/7/2009/H1N1-like virus vaccination on clinical manifestations and autoantibody profile in pSS. Methods: Thirty-six pSS patients and 36 gender/age-matched healthy controls were evaluated before and 21-days after vaccination with unadjuvanted influenza A/H1N1-like virus regarding seroprotection/seroconversion, factor increase in geometric mean titre (FI-GMT) and side effects. New onset of parotiditis, arthritis, vasculitis, pneumonitis or neurological disorders and autoantibody profile (ANA, RF, anti-dsDNA, Ro/SS-A/La/SS-B, alpha-fodrin, CCP, RNP/Sm, anticardiolipin) were assessed before, 21-days and 1-year of vaccination. Results: Patients and controls had similar rates of seroconversion (78 vs. 69%, p=0.42), seroprotection (83 vs. 72%, p=0.26) and FI-GMT (p=0.85). Disease duration, glucocorticoid (mean dose<10mg/day), methotrexate or azathioprine did not affect seroconversion (p>0.05). Interestingly, ANA positivity was more frequent in patients with seroconversion (100 vs. 71%, p=0.042). Regarding short-term side effects, only mild reactions were observed in comparable rates to controls (p>0.05). In the 1-year follow-up, the rate of new disease flares was similar to the previous year (11 vs.19%, p=0.51). Twenty-one days after vaccination, no change in the frequency or levels of autoantibodies was observed (p>0.05). Conversely, after 1-year, five patients developed positivity to anti-Ro/SS-A/La/SS-B, alpha-fodrin, CCP and/or IgM anticardiolipin. Of note, increase in titers only of anti-Ro and anti-La (p<0.001) was detected after 1-year. Conclusions: This is the first study to indicate appropriate influenza A/H1N1 vaccine safety and immunogenicity in pSS, reinforcing its recommendation. Further investigations are necessary to evaluate the clinical significance of long-term changes in autoantibody profile. Disclosure of Interest: S. Pasoto: None Declared, A. Ribeiro: None Declared, V. Viana: None Declared, J. Barbosa: None Declared, C. Bueno: None Declared, M. Levy Neto: None Declared, E. Bonfa Grant/Research support from: FAPESP grant: 2010/10749-0